Etude Sédimentologique Et Stratigraphique Des Dépôts Des Abris GAUDRY Et LARTET Du Gisement De Montgaudier, Charente, France - Mohammed, Boukhir; Faiza, Benjelloun; Abderrahim, Lahrach; Abdel-Ali, Chaouni (European Scientific Journal, ESJ, 2017)
The sedimentological and stratigraphic study of the two shelters: Gaudry and Lartet of the Montgaudier deposit made it possible to characterize the large sedimentary assemblages and to describe within each of the discontinuities revealed by the granulometric characteristics that have subdivided them into distinct layers. Moreover, the detailed sedimentological analyzes of these two shelters have led to the conclusion that the sediments are deposited under the cold climatic conditions alternated by the temperate episodes. On the other hand, the stratigraphic lithostratigraphic arguments allowed us to establish a stratigraphic relationship between the two shelters. From a chronological point of view, the deposits of the shelter Lartet appear to a Mousterian Charentian type contemporary to the old würm. As for the Gaudry shelter, layers 1 and 2 are contemporary with Magdalenian and layer 5 is attributed to the aurignacian. This is confirmed by an absolute date.